Travelling Wave Solutions of the Perturbed Wadati-Segur-Ablowitz Equation by (G'/G)-Expansion Method - Kangalgil, Figen (International Journal of Scientific Research and Management (IJSRM), 2018)
The investigation of the exact solutions of NLPDEs plays an im-portant role for the understanding of most nonlinear physical phenomena.Also, the exact solutions of this equations aid the numerical solvers to assessthe correctness of their results. In this paper, (G'/G)-expansion method is pre-sented to construct exact solutions of the Perturbed Wadati-Segur-Ablowitzequation. Obtained the exact solutions are expressed by the hyperbolic, thetrigonometric and the rational functions. All calculations have been made withthe aid of Maple program. It is shown that the proposed algorithm is elemen-tary, e¤ective and has been used for many PDEs in mathematical physics.